👤

a). (x²+[tex] \frac{x}{3} [/tex] ) - ([tex] \frac{x}{3} [/tex] + 2x ) + ([tex] \frac{5 x^2{} }{6} [/tex] - [tex] \frac{x}{4} [/tex] ) b). 2[tex] \frac{x}{3} [/tex]-([tex] \frac{4}{5} x^{2} [/tex]+[tex] \frac{2}{3} x[/tex] )+ (1[tex] \frac{2}{3} x^{2} + 0,(6)x)-0,2 x^{2} [/tex] va roooggg



Răspuns :

(x²+x/3 ) - (x/3 + 2x ) + (5x²/6 -x/4 )=
=x
²+x/3-x/3-2x+5x²/6-x/4=
=x²+5x²/6-2x-x/4= 
=11x
²/6-9x/4


b). 2 x/3-(4x
²/5+2x/3)+ (1 2x²/3+0,(6)x-0,2x²=
=2+x/3-4x
²/5+2x/3+ 1+ 2x²/3+2x/3-0,2x²=
=3+5x/3-4x²/5+ 2x²/3-x²/5=
=3+5x/3-x²+ 2x²/3=
=3+5x/3-x²/3